Body, Territory and Family in Afro-Colombian Communities Residing in Bogotá - Useche González, Gigson (Rastros Rostros, 2014)
This article is the result of the research study being conducted in the sub-area of research titled“Ethnoeducation: A Space for Rethinking Education in Colombia”, which is linked to the Facultyof Education at the Universidad Libre. It seeks to characterize the ethnic group made up of Afro-Colombian communities who are displaced in the country’s current political, economic and sociallandscape, and who are hurriedly inserted into the urban social fabric, thus damaging their quality of lifeand human development, and affecting the urban social dynamics. This situation merits both researchand pedagogical intervention in searching for and realizing educational proposals and life plans thatcontribute to the cultural and social rebuilding of these ethnic communities.
Keywords: afro-colombian communities; corporality; body; family; territory